Avenue of spies [large type] : a true story of terror, espionage, and one American family's heroic resistance in Nazi-occupied France - Kershaw, Alex (Random House Large Print, 2015)
The true story of an American doctor and his family in Paris, and his heroic espionage efforts during World War II. Exclusive Avenue Foch was Paris's hotbed of spies, secret police, informers, and Vichy collaborators. So when the couple at number 11--American physician Sumner Jackson and his Swiss-born wife Toquette--joined the French resistance, they knew the stakes were extraordinarily high. They would be risking not only their own lives but that of their only child, twelve-year-old Phillip. Toquette agreed to allow the Goelette network of the resistance to use their home as a drop box for vital information en route to Britain. As D-Day neared, the noose began to tighten.